Wizja tyrani w myśli Arystotelesa - Rubaj, Mateusz (PRAWO i WIĘŹ, 2025)
The paper presents an analysis of tyranny in Aristotle’s thought, presenting it as a form of government based on despotism and the self-interest of the ruler at the expense of the common good. The philosopher contrasts tyranny with a just monarchy, emphasizing its instability and negative impact on the state and society. The article discusses the origins of tyranny, its mechanisms for maintaining power, and the causes of its downfall. It also highlights the influence of ethics on tyranny in the context of Aristotle’s concept of the ideal state.